Association of the microsatellite (GT)n repeat polymorphisms of the HO-1 gene promoter and corresponding serum levels with the risk of laryngeal squamous cell carcinoma. (2nd August 2016) - Tang, Di; Tang, Wei-Jing; Shi, Xiao-Ling; Li, Wen-Ping; Zhou, Hong; Lu, Li-Ming; Tao, Lei
Abstract: Conclusion : Long (GT)n repeat polymorphisms in the heme oxygenase-1 (HO-1) gene promoter and decreased serum HO-1 levels are associated with a higher susceptibility to laryngeal squamous cell carcinoma (LSCC).Objective : In this case-control study, the association of HO-1 microsatellite (GT)n repeat polymorphisms and serum levels with the risk of LSCC was investigated.Methods : A total of 142 LSCC patients, 54 vocal leukoplakia patients and 98 healthy controls, were examined for (GT)n polymorphisms by sequencing, and the serum HO-1 levels were detected in a sub-set from participants above by ELISA.Results : Compared with the controls, the LSCC group had significantly higher frequencies of L-allele (> 29 repeats) and L-allele carriers ( p < 0.001, OR = 2.037 and p = 0.005, OR = 2.152, respectively). The frequencies of lymph node metastasis and of moderate or poor differentiation were significantly higher in L-allele carriers compared to non-L-allele carriers ( p < 0.05). Significantly lower serum HO-1 levels were detected in LSCC patients ( p < 0.001), and patients with lower serum HO-1 levels had more advanced cancer stage and a higher lymph node metastasis rate ( p < 0.05). Furthermore, the L-allele carriers had lower serum HO-1 concentrations compared with the non-L-allele carriers ( p = 0.019).